StressOnCampus: An App for Stress Management - Manuel Pambasange Jorge (U.Porto Journal of Engineering)
The goal of this study was to develop a mobile app that would be used as a self-help and stress-reduction tool for university students. The StressonCampus app adopted a hybrid questionnaire based on the DASS-21 and Kessler PT models, which identifies the level of stress and, likewise, provides suggestions for relaxation exercises. The improved version of the app includes a chatbot or conversation agent that allows a dialogue with the student to detect the student's stress situation and present a relaxation recommendation based on it.